2009
DOI: 10.2134/agronj2008.0230x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Necessity of Surface‐Applied Preplant Nitrogen Fertilizer in Rice Systems

Abstract: California rice (Oryza sativa L.) growers typically use two forms of preplant N fertilizer: aqua NH 3 applied 7 to 10 cm below the soil surface (subsurface N) and surface-applied N. Th e rational for applying about 25% of the total N rate to the surface is to provide a readily available N source for young rice seedlings; however no research has been done to verify this. On-farm fi eld studies were conducted over a 3-yr period (12 site-years) with the specifi c objectives of determining when rice begins to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 21 publications
4
38
2
Order By: Relevance
“…On the basis of a review of mostly Asian rice fields by Akiyama et al (2005), the IPCC (Eggleston et al, 2006) determined the default N 2 O emissions from continuously flooded rice fields to be 0.003 kg N 2 O‐N kg −1 N applied. Assuming a typical fertilizer N rate of 170 kg N ha −1 for US rice fields (Linquist et al, 2009), this would amount to 0.51 kg N 2 O‐N ha −1 season −1 , which is six times higher than reported here. Lower N 2 O emissions in US rice systems relative to Asian rice systems may be due to better water control, which ensures that fields remain flooded when desired.…”
Section: Resultsmentioning
confidence: 59%
“…On the basis of a review of mostly Asian rice fields by Akiyama et al (2005), the IPCC (Eggleston et al, 2006) determined the default N 2 O emissions from continuously flooded rice fields to be 0.003 kg N 2 O‐N kg −1 N applied. Assuming a typical fertilizer N rate of 170 kg N ha −1 for US rice fields (Linquist et al, 2009), this would amount to 0.51 kg N 2 O‐N ha −1 season −1 , which is six times higher than reported here. Lower N 2 O emissions in US rice systems relative to Asian rice systems may be due to better water control, which ensures that fields remain flooded when desired.…”
Section: Resultsmentioning
confidence: 59%
“…On average, 40% (range, 31–52%) of fertilizer N was taken up by the rice crop, similar to what has been reported for rice by others (Ladha et al, 2005). Based on the N difference method, Linquist et al (2009) found that 49% of the N applied was recovered in California rice systems; however, N recovery based on the 15 N‐dilution method is on average 11% higher than that suggested by the N difference method (Ladha et al, 2005). During the course of the year, 36.5 to 38% of the applied fertilizer N was lost.…”
Section: Discussionmentioning
confidence: 95%
“…Although the N rate is typical for California, the method of application differs. In most cases, 70 to 80% of the N is applied as aqua‐ammonia about 7.5 cm below the soil surface (Linquist et al, 2009). The remaining fertilizer N is usually applied to the soil surface before planting as a blended fertilizer containing P and K as well as some N (usually as ammonium sulfate or ammonium phosphate).…”
Section: Methodsmentioning
confidence: 99%
“…Typically in Asia, rice is transplanted and fertilizers are applied into flooded water; however, the general trend in Asian rice systems is toward direct seeding (Rao et al, 2007). In direct water‐seeded systems such as those found in California, much of the fertilizer N is injected into the soil as aqua‐NH 3 before planting (Linquist et al, 2009). Some N and the P and K fertilizers are usually applied to the soil surface at the same time and may or may not be incorporated into the surface soil.…”
mentioning
confidence: 99%